Pemberdayaan Ibu dan Keluarga melalui Media Leaflet untuk Mencegah Stunting dengan Meningkatkan Pengetahuan Gizi dan Pengelolaan Pendapatan Rumah Tangga - Meidayana Refisiliyani (PPNI UNIMMAN, 2025)
Stunting is a chronic nutritional issue that significantly affects children's long-term growth and development. One of its primary causes is the lack of knowledge among mothers and families about balanced nutrition and the skills to manage household income effectively. This community engagement program aimed to enhance the knowledge of mothers and families through leaflet-based education on child nutrition and household income management for stunting prevention.The activity was conducted in the working area of Puruk Cahu Public Health Center, Central Kalimantan, involving 30 housewives with children under five years old. The education was delivered through lectures using both leaflet and PowerPoint media, and the implementation consisted of three stages: preparation, implementation, and evaluation. The results showed that empowering mothers and families through leaflet media is an effective educational strategy. After the intervention, participants showed a significant improvement in understanding the importance of early nutritional intake, the concept of balanced nutrition, and simple strategies for managing household finances to meet their children's nutritional needs. In addition, participants became more aware of the family's active role in ensuring quality food consumption for children and the long-term impacts of malnutrition.It is expected that this increased knowledge will enable mothers and families to become agents of change in preventing stunting and fostering an environment that supports optimal child growth and development.